2011
DOI: 10.1159/000330016
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Transcranial Magnetic Stimulation in the in vivo Functional Evaluation of Central Cholinergic Circuits in Dementia

Abstract: Central cholinergic circuits of human brain can be tested non-invasively by coupling electrical peripheral stimulation with transcranial magnetic stimulation (TMS) of the motor cortex. The short-latency afferent inhibition (SAI) is reduced in cholinergic forms of dementia, such as Alzheimer disease (AD) and dementia with Lewy bodies, while it is normal in non-cholinergic forms of dementia, such as frontotemporal dementia. This finding suggests that this method can be used as a non-invasive additional tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 129 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…SAI is reduced in cholinergic forms of dementia, while it is normal in non-cholinergic forms of dementia [18]. The amount of SAI was found to be decreased in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy and cognitive impairment [19].…”
Section: Introductionmentioning
confidence: 94%
“…SAI is reduced in cholinergic forms of dementia, while it is normal in non-cholinergic forms of dementia [18]. The amount of SAI was found to be decreased in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy and cognitive impairment [19].…”
Section: Introductionmentioning
confidence: 94%
“…In a recent paper aiming at the evaluation of short-latency afferent inhibition in a sample of VCI-ND patients with predominant WMLs, central cholinergic circuitry was found to be not clearly involved in patients compared to age-matched controls [95], suggesting a distinctive profile of the cholinergic pathway with respect to primary cholinergic forms of dementia (namely, AD), even in the early stage [99]. A reasonable explanation is that VCI may exhibit considerable interindividual variation in the location of subcortical infarcts and, therefore, in the distribution and magnitude of the resultant cholinergic denervation [100]. This study also supports the role of short-latency afferent inhibition in providing useful insight in the diagnosis and prognosis of different dementing process and in the identification of responders to acetylcholinesterase inhibitors [95].…”
Section: Tms Correlates Of Vci Subtypesmentioning
confidence: 99%
“…[6] The threshold of motor response is an index of excitability of the corticospinal motor neurons and the amplitude of the motor response and duration of silent period (SP) is related to cortical inhibition mediated through gamma-aminobutyric acid (GABA)-B receptors. Using a study performed in fifteen patients with a single pulse stimulation the authors found the following changes in Alzheimer's disease using the short-latency afferent inhibition (SAI), which is produced by inhibitory interactions within the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%